Design of Mechanized Nanocomposites for Exploring New Chemical Motions. Issue 9 (12th August 2019) - Cho, Wansu; Park, Chiyoung
Abstract: The history of organic chemistry has evolved from the discovery of new things to the creation of more complex and unique composites. Mechanized composites are materials constructed by mechanically controlling the structure to obtain other structures or functions through combination. Recent advances in the field have shown that the mechanochemical engineering of polymers has enabled the exploration of new reaction pathways, which is impossible or too complicated to achieve with conventional methods. In addition, molecular machines equipped on nanomaterials exhibit superior or unexpected functions for transport phenomena, which are useful for biomedical and electronic applications. Despite the many contributions toward understanding mechanized nanocomposites, acquiring fundamental knowledge and conducting experiments are still necessary for achieving unexplored applications. Herein, we describe recent advances in mechanized nanocomposites in terms of design for specific applications. Abstract : Recent examples for mechanized nanocomposites have shown performances such as controlling energy dissipation and transport phenomena. As this research field is still in its infancy, research on mechanized nanocomposites requires revealing fundamental phenomena along with exploring new applications, which cannot be achieved with known chemical systems.